PENDAMPINGAN LESSON STUDY UNTUK MENGEMBANGKAN KOMPETENSI GURU SEKOLAH DASAR MENGINTEGRASIKAN NILAI KARAKTER PADA PEMBELAJARAN MATEMATIKA - I Gusti Ngurah Japa; Komang Sujendra Diputra (Universitas Sriwijaya, 2019)
AbstractThis activity is a community devotion that aims to give understanding to elementary school teachers in designing and implementing integrated mathematics learning of character education. Partners in this activity are teachers of elementary school in group VIII of Sawan subdistrict. Activities were conducted through participatory persuasive approaches, which began with workshops and followed by a lesson study. The results of this activity show that the lesson study was able to improve the skills of SD teachers in designing and execute integrated mathematics learning of character education proven RPP score and the implementation of learning is in